2019
DOI: 10.3390/app9214509
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of ZnO Thin Films Grown on Quartz Glass and Sapphire (001) Substrates by Means of Magnetron Sputtering and High-Temperature Annealing

Abstract: In this work, we reported a comparative study of ZnO thin films grown on quartz glass and sapphire (001) substrates through magnetron sputtering and high-temperature annealing. Firstly, the ZnO thin films were deposited on the quartz glass and sapphire (001) substrates in the same conditions by magnetron sputtering. Afterwards, the sputtered ZnO thin films underwent an annealing process at 600 °C for 1 h in an air atmosphere to improve the quality of the films. X-ray diffraction, scanning electron microscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…While, no other peaks that belong to ZnO can be seen in the XRD pattern. The similar behavior was also observed in another report that was presented by Yang et al [ 34 ] on the growth of ZnO thin films on sapphire (001) substrates. They showed that only two peaks thatcontributed to the (002) and (004) planes of ZnO were observed.…”
Section: Resultssupporting
confidence: 89%
“…While, no other peaks that belong to ZnO can be seen in the XRD pattern. The similar behavior was also observed in another report that was presented by Yang et al [ 34 ] on the growth of ZnO thin films on sapphire (001) substrates. They showed that only two peaks thatcontributed to the (002) and (004) planes of ZnO were observed.…”
Section: Resultssupporting
confidence: 89%
“…The ZnO films transparency measurements for electromagnetic wavelengths from the visible light range did not show the influence of the production process temperature on their transparency (Figure 9). In the case of the tested samples, high transparency in the range of 80-90% for visible light, electromagnetic wavelengths above 400 nm was observed, which corresponds to the results achieved by earlier investigations [27,28]. Graph course for a sample deposited at a temperature of 300 • C is different from 100 • C and 200 • C. This is in line with the ellipsometer thickness results (the film produced by 300 • C is thicker than the rest) and the AFM results of the roughness parameters.…”
Section: Resultssupporting
confidence: 89%
“…The small abnormality of the scoreline is credited to the presence of excess zinc in the film . The reported Zn 2p 3/2 core-level range is 1021.24–1021.81 eV, which is associated with Zn 2+ ions . The Zn 2p 3/2 binding energy electronic states are the same as the reported value of the bulk ZnO (1021.8 eV) .…”
Section: Resultsmentioning
confidence: 60%
“…45 The reported Zn 2p 3/2 core-level range is 1021.24−1021.81 eV, which is associated with Zn 2+ ions. 46 The Zn 2p 3/2 binding energy electronic states are the same as the reported value of the bulk ZnO (1021.8 eV). 46 No metallic Zn peak was found, which confirms that Zn exists only in an oxidized state.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation